Assessment of Information Needs of Dairy Farmers about Dairy Farming in Karnataka - Shivalika; Rathod, Prakashkumar; Anjali; Biradar, Channappagouda (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted to determine the information needs of dairy farmers about dairy farming with a sample size of 200 respondents from Karnataka. Purposive and random sampling method was adopted. The statistical techniques used were frequency, percentage, weighted mean score, ranking, index value, mean index value and independent student t test. The study revealed that there was a significant difference (p<0.05) between North and South Karnataka dairy farmers with regards to information needs on the following major areas, viz., breeding and reproduction, housing management etc., Information on marketing and finance was ranked first by majority of North region farmers, whereas, information on health management and disease control was ranked first by farmers of South region. Overall index value indicated that, information on marketing and finance was ranked first, by all the dairy farmers. The current study emphasizes the importance of information need assessments studies and also need to develop relevant strategies, particularly before developing any ICT based web modules.